PENGARUH DISIPLIN KERJA, KEPUASAN KERJA, DAN MOTIVASI TERHADAP KINERJA KARYAWAN (Studi Pada CV GARUDA PLASTIK KURIPAN DEMAK) - Niti Dwi Rahma Ningrum, 15.05.51.0274 (Students' Journal of Economic and Management, 2019)
This study aims to test and analyze the effect of Work Discipline, Job Satisfaction and Motivation on employee performance. The analytical tool used is multiple regression, while to test the hypothesis using the t test. Data collection through questionnaires with measurements using a Likert scale 5 (five) alternative answers. The object of research is CV employees. Garuda Plastic Demak Demak. The number of samples in this study were 87 respondents. The sampling technique uses simple random sampling. The results showed that (1) Work Discipline had a positive and significant effect on employee performance (2) Job Satisfaction had a significant positive effect on employee performance, (3) Motivation did not affect employee performance.